2009
DOI: 10.1002/yea.1727
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence for a role of Saccharomyces cerevisiae Mph1 in recombinational DNA repair under replicative stress

Abstract: In yeast as in human, DNA helicases play critical roles in assisting replication fork progression. The Saccharomyces cerevisiae MPH1 gene, homologue of human FANCM, has been involved in homologous recombination and DNA repair. We describe a synthetic growth defect of an mph1 deletion if combined with an srs2 deletion that can result -depending on the genetic background -in synthetic lethality. The lethality is suppressed by mutations in homologous recombination (rad51, rad52, rad55, rad57 ) and in the DNA dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 92 publications
2
18
0
Order By: Relevance
“…3; Supplemental Fig. 2; Scheller et al 2000;Schurer et al 2004;Panico et al 2010). MTE1 deletion did not increase cell sensitivity (Lisby et al 2003).…”
Section: Deletion Of Mte1 Suppresses the Mms Sensitivity Of Mph1δ Mutmentioning
confidence: 91%
See 2 more Smart Citations
“…3; Supplemental Fig. 2; Scheller et al 2000;Schurer et al 2004;Panico et al 2010). MTE1 deletion did not increase cell sensitivity (Lisby et al 2003).…”
Section: Deletion Of Mte1 Suppresses the Mms Sensitivity Of Mph1δ Mutmentioning
confidence: 91%
“…Importantly, on its own, Mte1 did not catalyze these reactions. Second, we tested the impact of Mte1 on the ability of Mph1 to displace D loops (Prakash et al 2009;Panico et al 2010;Zheng et al 2011). A D loop was formed by Rad51-catalyzed invasion of a 5 ′ -radiolabeled 90-mer oligo D1 into a homologous negatively supercoiled dsDNA plasmid (pBSC) in the presence of Rad54 (Sebesta et al 2011).…”
Section: Deletion Of Mte1 Suppresses the Mms Sensitivity Of Mph1δ Mutmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic analyses have shown that simultaneously removing any two of these helicases increases crossover level more than ablating just one of them (Prakash et al 2009;Mitchel et al 2013). Nonoverlapping DNA repair roles between Mph1 and either Sgs1 or Srs2 lead to synthetic sickness or lethality of double mutants upon DNA damage occurrence (St Onge et al 2007;Chen et al 2009;Panico et al 2010). Similarly, Mph1 and STR orthologs in fission yeast and A. thaliana also have independent functions in crossover control and/or DNA repair (Sun et al 2008;Knoll et al 2012;Seguela-Arnaud et al 2015).…”
Section: Fancm Regulation By Faap24 and Kinasesmentioning
confidence: 99%
“…Sc-MPH1 is epistatic to a number of budding yeast homologous recombination (HR) genes, and the somatic HR rate is increased in mph1 mutant cells (Schürer et al, 2004). Recently, it was shown that Mph1 participates in D-loop formation in HR, together with the recombinase Rad54 (for radiation sensitive54) (Panico et al, 2010;Ede et al, 2011). In double mutants of MPH1 and SGS1 (for slow growth suppressor1), the sole budding yeast RecQ helicase homolog, the HR rate is higher than the rate of either single mutant, indicating two separate pathways with Mph1 and Sgs1 functioning in either one to suppress somatic HR (Schürer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%